Importance of the neutrophil-to-lymphocyte ratio as a marker for microbiological specimens in critically ill patients after liver or lung transplantation. - Wiegand, Steffen B.; Paal, Michael; Jung, Jette; Guba, Markus; Lange, Christian M.; Schneider, Christian; Kneidinger, Nikolaus; Michel, Sebastian; Irlbeck, Michael; Zoller, Michael (Infection, 2025)
Purpose: The correct and early diagnosis of an infection is pivotal for patients, especially if the patients are immunocompromised. Various infection markers are used in clinics with different advantages and disadvantages. The neutrophil-to-lymphocyte ratio (NLR) is a cost effective parameter easily obtained without further investments. The aim of this study is to elucidate the value of the NLR in comparison to other established inflammation markers in patients in the intensive care unit who underwent liver or lung transplantation for the detection of bacterial and fungal specimens. Methods: In this retrospective single centre study infection marker and microbiology data of 543 intensive care cases of liver or lung transplanted patients in the intensive care unit after transplantation were analysed. Results: In total 5,072 lab work results and 1,104 positive microbiology results were analysed. Results of an area under curve analysis were better for the NLR (0.631; p < 0.001) than for CRP (0.522; p = 0.152) or IL-6 (0.579; p < 0.001). The NLR was independent of type of organ which was transplanted and gender of patients, whereas IL-6 values differed significantly between liver and lung transplanted patients and between male and female. Conclusion: All analysed inflammation markers are far from being perfect. The NLR is a sensitive marker with reasonable threshold for the detection of microbiological specimens independent of gender or type of organ transplanted. The use allows a more differentiated approach to face the challenge of bacteria and fungus in patients who underwent liver or lung transplantation.